The Role of Youth in The Development of Malay Culture-Based Tourism Destinations in Langkat Regency, North Sumatra Province - Prana, Hendi; Sibarani, Robert; Suryanto , Dwi (TALENTA Publisher, Universitas Sumatera Utara, 2021)
The purpose of this study is to find out how the Azizi Mosque as a Malay-based tourist destination and to determine the extent of the role of youth DPD KNPI Langkat in the development of tourism destination based malay culture in Langkat of North Sumatera Province. The results of this study are based on observational data that researchers do is that the Azizi Mosque is a building that contains historical and cultural values of Malay in Langkat district, where, in addition to the architectural splendor of the Azizi mosque building with its wide area that fascinates tourists, the Azizi mosque building ornaments also is a symbol or shows the characteristics of Malay culture in Langkat district. There is also a complex surrounding the tombs of the kings or sultans who once ruled the sultanate period langkat. Even according to historical records collected by researchers, the Azizi Mosque was once functioned as the Langkat Sultanate Palace. Until now, Azizi is a building that has witnessed the glory of the Langkat sultanate in the past.